The Influence Of Multiple Intelligence Toward English Learning Outcomes Of The Seventh Grade At SMPS IT Mutiara - Rizka Nazifah, Tengku; Setiawati (Jolly Journal of English Education, 2023)
This study aims to determine the significant influence of multiple intelligences on English learning outcomes in seventh grade at SMPS IT Mutiara. To find out the significant influence the researcher used research with survey methods with a quantitative approach. The population of the study was seventh grade students at SMPS IT Mutiara with a total of 193 students, consisting of seven classes. Due to the large number of population, the researcher took a sample of 127 students from all seventh graders. The data collection technique that the researcher uses is in the form of non-test, namely multiple intelligence questionnaires and documentation in the form of student reports in odd semesters (I). The results of the study of the significant influence of multiple intelligence on English learning outcomes can be seen from, this is known from hypothesis testing using a stimulant test (F test). Where, the result of F count of 9.608 > F table 3.92, with a p value of 0.002 < 0.05. This was in accordance with the criteria from the F test which said P < 0.05, so there was a significant Influence of Multiple Intelligence toward English learning outcomes